2022
DOI: 10.1186/s13014-022-02157-5
|View full text |Cite
|
Sign up to set email alerts
|

A dual deep neural network for auto-delineation in cervical cancer radiotherapy with clinical validation

Abstract: Background Artificial intelligence (AI) algorithms are capable of automatically detecting contouring boundaries in medical images. However, the algorithms impact on clinical practice of cervical cancer are unclear. We aimed to develop an AI-assisted system for automatic contouring of the clinical target volume (CTV) and organs-at-risk (OARs) in cervical cancer radiotherapy and conduct clinical-based observations. Methods We first retrospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Previously, studies have reported the results of autosegmentation of OAR/CTVs in cervical cancer (15,(23)(24)(25)(26). One study including 100 cases for model training reported similar results to those of our study for OARs (24).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previously, studies have reported the results of autosegmentation of OAR/CTVs in cervical cancer (15,(23)(24)(25)(26). One study including 100 cases for model training reported similar results to those of our study for OARs (24).…”
Section: Discussionsupporting
confidence: 84%
“…A study by Li et al employed quantitative metrics, including the DSC, HD, and true positive volume fraction, to analyze the contours of the CTV, bladder, rectum, bowel bag, and femoral head in postoperative cases. The DSC values ranged from 0.84 to 0.93 (25). In another study, in addition to DSC and HD, the Jaccard coefficient and dose-volume index were utilized for dosimetric evaluation of the spinal cord, kidney, bladder, femoral head, pelvic bone, rectum, and small intestine (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep‐learning‐based (DL) methods using Convolutional neural networks (CNN) have been applied to the segmentation of images of a variety of cancers 6–8 . In terms of cervical cancer, it has shown comparable performance to the expert delineation for some cervical cancer segmentation 9–14 . However, the performance of these auto‐segmentation networks is highly dependent on the training dataset, which is affected by the difference in physician contouring styles and the anatomic structure differences among patients 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 8 In terms of cervical cancer, it has shown comparable performance to the expert delineation for some cervical cancer segmentation. 9 , 10 , 11 , 12 , 13 , 14 However, the performance of these auto‐segmentation networks is highly dependent on the training dataset, which is affected by the difference in physician contouring styles and the anatomic structure differences among patients. 15 , 16 In order to generalize the trained network to a variety of unseen patient cases, network training is usually based on a large enough training set of different patient cases.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2023) devised novel Inner Cascaded U-Net and Inner Cascaded U2-Net as improvements to plain cascaded U-Net for medical image segmentation, achieving better segmentation performance in terms of dice similarity coefficient and hausdorff distance as well as getting finer outline segmentation. Nie et al (2022) proposed a method named SegNet that was developed and trained with different data groups. Quantitative metrics and clinical-based grading were used to evaluate differences between several groups of automatic contours.…”
Section: Introductionmentioning
confidence: 99%